2015
DOI: 10.1159/000430158
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-Catenin and Wnt5a/Ca2+ Pathways Regulate Proliferation and Apoptosis of Keratinocytes in Psoriasis Lesions

Abstract: Background/Aims: Wnt5a is overexpressed in psoriasis lesions, however the mechanism by which Wnt5a is involved in the pathogenesis of psoriasis is not clear. To address this, the expression of Wnt5a in psoriatic lesions and its effect on keratinocyte cell proliferation and apoptosis was examined in vitro. Methods: The expression levels of WNT5A, and genes encoding its receptors frizzled2 (FZD2) and frizzled5 (FZD5) were examined in samples obtained from individuals with psoriasis and healthy controls. Knockdow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 37 publications
3
49
1
Order By: Relevance
“…During the implantation window, appropriate apoptosis of the uterine epithelium and stromal cells facilitates embryo attachment to the endometrial epithelium and the subsequent invasion into the endometrial stroma (Boeddeker & Hess, ). Zhang et al () found that knocking down WNT5A induces apoptosis by inhibiting WNT/β‐catenin. Griesmann et al () also proved that knocking down WNT5A significantly increases drug‐induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…During the implantation window, appropriate apoptosis of the uterine epithelium and stromal cells facilitates embryo attachment to the endometrial epithelium and the subsequent invasion into the endometrial stroma (Boeddeker & Hess, ). Zhang et al () found that knocking down WNT5A induces apoptosis by inhibiting WNT/β‐catenin. Griesmann et al () also proved that knocking down WNT5A significantly increases drug‐induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis is a result of the interaction of genetic predisposition and external stimuli including stress, infection, trauma, and drugs [2][3][4]. This disease is characterized by a series of linked cellular changes in the skin, including hyperproliferative keratinocytes, parakeratosis, hyperkeratosis, and infiltration of inflammatory leukocytes into the dermis and epidermis, resulting in a thickened epidermis [5,6]. The mechanism of psoriasis is still not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…The body adjusts keratinocyte proliferation and regulates the growth and differentiation of epidermal cells through apoptosis. Apoptosis offsets keratinocyte proliferation and regulates the formation of stratum corneum, and improper functioning of apoptotic pathways leads to the development of several skin diseases . Psoriatic keratinocytes exhibit an enhanced ability to resist apoptosis, which may be one of the key factors in the pathogenesis of psoriasis, while metformin is known as an antiproliferation drug in major cell lines and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis is a common chronic inflammatory disease which is characterized by abnormal proliferation and differentiation of keratinocytes . Although the exact mechanism of psoriasis is not yet clearly understood, the enhanced proliferation of keratinocytes and inflammation are considered to be the key events that contribute to its development . Therefore, inhibition of excessive proliferation of keratinocytes may lead to the prevention and treatment of psoriasis.…”
Section: Introductionmentioning
confidence: 99%